Reliability and validity of a submaximal shuttle running test for elite athletes - Leicht, A.; Dobbin, M.; Sinclair, W.; Doma, K.; Simmons, R. (Defence Human Sciences Symposium, 7-9 December 2020, 2020)
Background: Elite athletes such as those in team sports and military undertake regular training to maintain and enhance performance. Regular monitoring of training adaptations provides practitioners with important feedback to optimise training. However, maximal exercise assessment protocols may contribute to fatigue accumulation and subsequent poorer training responses and/or performance. The use of submaximal testing protocols may provide practitioners with a superior tool to identify training adaptations without subsequent impact. Recently, a submaximal shuttle running test (SubRT) was developed to monitor elite athletes with its reliability and validity yet to be determined. Aims: To examine the reliability and validity of the SubRT in elite athletes. Method: Twenty-nine, male athletes from the same organisation volunteered and completed the SubRT three times (1-2 weeks between trials) and a field-based test of aerobic fitness/capacity. The SubRT consisted of: 8 x 40m shuttle runs (shuttle/15 seconds); 30 seconds of standing recovery; 8 x 50m shuttle runs (shuttle/15 seconds); and 60 seconds of standing recovery. Heart rate (HR) was recorded continuously via a telemetric system during the SubRT with peak and mean HR during each running and recovery bout recorded. The HR decline during recovery was examined in absolute and relative terms, as well as the slope of change. For the assessment of aerobic fitness/capacity, participants completed an intermittent shuttle run test (ISRT, five bouts of continuous running of 2 x 20m, 2 x 40m and 2 x 60m until a total distance of 1200m was completed in the quickest time). Reliability of the SubRT was determined by 1-way ANOVAs, intraclass correlation coefficients (ICC), coefficient of variation (CV), and measurement bias with 95% limits of agreement (LOA). Validity was determined from Pearson correlations between SubRT variables and ISRT time. Results: Repeated SubRT trials resulted in similar mean running HR for each trial but significantly lower peak HR for running bouts one (149.8 8.5 vs. 154.4 10.0 bpm) and two (164.7 7.3 vs. 168.7 8.9 bpm) during the second compared to the first trial. Likewise, the mean HR during recovery bouts one (137.6 13.3 vs. 148.3 13.1 bpm) and two (143.1 9.1 vs. 154.9 10.3 bpm) were significantly lower for the second compared to the first trial. The absolute and relative HR decline during recovery bouts were significantly greater for trial two compared to trials one and three. When comparing SubRT trials, the ICC for peak and/or mean HR during running (>0.74) and recovery (>0.42) bouts were moderate to good while the CV (2-8%) and measurement bias and LOA were small moderate. In contrast, the ICC and CV for the absolute/relative and rate of HR decline during recovery were poorer. Validity for the SubRT was weak with the peak HR difference between running bouts within the same SubRT trial significantly correlated with ISRT time (>-0.51, p<0.01). Conclusions: This study demonstrated good reliability of the SubRT in terms of running and recovery peak and mean HR for elite athletes. Limited validity of the SubRT as an indicator of aerobic fitness/capacity was observed with further work needed to clarify this aspect.